DIVERSITAS SOSIOKULTURAL DALAM PENDIDIKAN MULTIKULTURAL DAN GENDER - KOSASSY, SITI OSA (Pelita Bangsa Pelestari Pancasila, 2016)
Indonesia is a pluralistic country that there are various tribes from Sabang to Merauke. As a result of this diversity conflicts often occur that are horizontal, such as the conflict in Poso, Sampit conflict, ethnic violence in China in 1998 and various other conflicts that resulted in deaths. Besides pluralism in Indonesia, there are also shades of the gender differences between men and women in various ways, such as education, the working world and others. to solve it is necessary for multicultural education and gender. Multicultural education as a new paradigm that was born in the late twentieth century had a vision and a program to prepare young people to face the global world community in a multicultural frame. Multicultural education as a program designed based on the dimensions: content integration, knowledge construction, prejudice ruduction, equitable pedagogy, and empowering school culture and social structure. So, the school must teach how multicultural education and gender to eliminate all the differences that occur in the community and make life full of peace and tolerance.